Preparo do solo e crescimento de Eucalyptus grandis Hill ex Maiden. em argissolo - Prevedello, Juliana (2008)
The Eucalyptus plantation is growing fast in south Brazil due its easy clime adaptation and diverse use of its wood. The ecosystems where the expansion is going on are fragile to anthropic action implying in a need of careful planning to set forest projects. One of important steps is the soil tillage used to implant forests which may have as main concern create a good soil environment to initial plant growth at same time prevent soil degradation. The objective of this study was to evaluate soil physical changes and its effects on initial growth of Eucalyptus grandis Hill ex Maiden. caused by several soil tillage too implant a forest. The experiment was set up at experimental area of FEPAGRO FLORESTAS, a state forest research center located at Santa Maria county, state of Rio Grande do Sul in a Hapludalf soil. The experimental design was a complete randomized block with three replication and four treatments as follow: PD no-tillage; Esc chisel plow; EG chisel plow plus harrowing and; ER rotary plow (rotary tiller). The Eucaliptus was planted in November of 2006. The soil physical properties were measured three times and growth parameters four times throughout first twelve months. The plantation without tillage caused a initial Eucaliptus growth in soil with higher soil resistance and bulk density and smaller macroporosity, as compared to tillage which mobilized soil. The physical condition at inter-row presented more restrictive conditions. The aggregate stability showed results suggesting some degradation condition, however, did not caused critical values. The soil tillage with mobilization resulted in better initial growth of Eucalyptus grandis.